A Newton-like method for the numerical solution of nonlinear Fredholm-type operator equations - Kohaupt, L. (Applied mathematics and computation, 2012)
In a recent paper, Hernández and Salanova proposed an interesting Newton-like method for the solution of nonlinear Fredholm integral equations. The aim of the present paper is to carry over this method to nonlinear operator equations of similar type. By using a functional analytic approach, the presentation becomes much clearer and more general. Apart from this, some new results in the Banach space setting as well as in the applications are obtained.